Teacher and Student Well-being in the Covid-19 pandemic - Full report - Dharan V; Pond R; Mincher N; Muralidharan V (Massey University, 2022)
This project sought to understand the perspectives of teachers and students in the lower North Island of Aotearoa New Zealand at the time of the first COVID-19 pandemic lockdown in March 2020 and during the following several months. Thirteen teachers from seven schools in the Manawatū-Horowhenua and Greater Wellington area and seven focus groups of Year 4 to 8 students from four of the schools participated in this project. This final report includes the findings from teachers and students’ perspectives of the affordances and challenges of lockdown and subsequent return to school, and their perspectives on helpful strategies in the event of similar situations given the unpredictable times. Analysis of teachers’ perspectives highlighted three interrelated themes –Stepping up Ngāwhiringatanga; Building Resilience and Reflecting and Recalibrating. The lockdown provided teachers time for introspection and have some time for their own personal well-being and growth. Although the challenge of adapting to online teaching sessions was stressful, the increased knowledge of the impact of COVID-19 on families and communities, had a profound impact on ongoing pedagogy of teachers. Teachers were resilient to the challenges and supported the resilience and well-being of students both during lockdown and on their return to school. They were supported by their school systems to ease pressure on academic learning and focus on holistic well-being of students such as spending quality time with their families. The lockdown highlighted the importance of work life balance, with teachers experiencing the benefits of having the time and space to focus on their personal well-being, which is critical for the well- being of their students, enabling them to support their students becoming resilient in the face of adversities caused by the ongoing presence of the pandemic. The students’ on the other hand while feeling isolated from their peers and anxious about the effects of the virus on their near and dear ones, appreciated the quality time that they could spend with their families and pets, and more importantly the flexibility that lockdown offered in terms of their learning. The key inter-related themes from their perspectives were: worry about safety and changes; restrictions and isolation; freedom and autonomy; friendship and connection; and quality family time.